Marketing mix strategy to increase B2C volume at XXX (Logistic Company) - Wibowo, Annisha Ananda Putri; Aprianingsih, Atik (Penerbit Goodwood, 2024)
Purpose: This study develops and analyzes marketing mix strategies to enhance the B2C (business-to-consumer) segment of XXX, a leading logistics and delivery service provider in Indonesia. This study focuses on identifying the challenges in increasing daily shipment volumes and evaluating the effectiveness of current marketing strategies. Research Methodology: This study employs both quantitative and qualitative methods, including surveys, observations, and documentation. Data were collected from 214 respondents using structured questionnaires distributed through Google Forms. Structural Equation Modeling (SEM) with Smart PLS software was utilized to analyze the relationships between the 7Ps of marketing (Product, Price, Place, Promotion, People, Physical Evidence, and Process) and consumer attitudes and purchase intentions Results: The findings indicate that product quality, pricing strategies, promotional activities, and customer service significantly affect consumer satisfaction and brand loyalty. Efficient processes also play a crucial role in shaping consumers’ attitudes and purchase intentions. The study reveals that, while promotional activities and physical evidence have a lesser impact, elements such as products, prices, people, and processes are essential in driving positive consumer attitudes and purchasing decisions. Conclusions: The majority of XXX’s customers in Indonesia are young to middle-aged women with a bachelor's degree, working as private employees, and typically spending modest amounts on shipping, indicating infrequent usage. The study found that product quality, employee performance, and process efficiency significantly influence consumer attitude intention, which strongly drives purchase intention. Price, distribution, promotion, and physical evidence, however, were not found to significantly impact consumer attitudes. Limitations: This study is limited to XXX operations in Indonesia and focuses solely on the impact of marketing mix elements on consumer attitudes, intentions, and purchase decisions. Future research could explore other logistics companies and encompass a broader geographical focus. Contribution: This study provides practical recommendations for XXX to enhance its market share in the B2C segment.